Analyzing Aseity. Issue 2 (February 2020) - Adams, Sarah; Robson, Jon
Abstract: The doctrine of divine aseity has played a significant role in the development of classical theism. However, very little attention has been paid in recent years to the question of how precisely aseity should be characterized. We argue that this neglect is unwarranted since extant characterizations of this central divine attribute quickly encounter difficulties. In particular, we present a new argument to show that the most widely accepted contemporary account of aseity is inconsistent. We then consider the prospects for developing a new account of aseity which avoids the pitfalls we have highlighted.